Evaluación de la extracción de colágeno en las secciones de cuello y falda de las pieles de bovinos (2020)
This evaluation was carried out through a bibliographic review, which aims to establish the most appropriate extraction method between the enzyme, chemical and mixed method, this selection was made using a decision matrix defined by three criteria such as operating costs, process efficiency and variables to be controlled in the process, the chemical method is selected and based on the information collected is made a proposal for main equipment for a pilot plant level escalation and the feasibility and profitability of the project was determined.